2019
DOI: 10.1139/cjm-2018-0612
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microbial communities of a passive coal mine drainage bioremediation system

Abstract: Drainage from abandoned mines is one factor greatly affecting the streams and vegetation in and around Pittsburgh and the Appalachian Mountains where coal mining occurred. This drainage may be more acidic, alkaline, or metal based. Different methods for remediation exist. Passive remediation is one method used to naturally allow the metals to precipitate out and aid in cleaning up the water. The goal of this study is to sample different holding ponds in a sequential passive remediation system and determine mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Similarly, passive bioremediation system enriched with Ignavibacterium, Pelotomaculum, and Petrimonas and species known to catalyse the dissimilatory reduction of ferric iron (Geobacter psychrophilus), oxidation of sulfur (Polaromonas hydrogenivorans, Flavobacterium johnsoniae, Dechloromonas aromatica, Novosphingobium sediminicola, Clostridium saccharobutylicum, and Pseudomonas extremaustralis), and reduction of nitrate (Sulfuricella denitrificans, A. ferrooxidans, and Acidithiobacillus thiooxidans), methylotrophs (methane/methanol-oxidizers), and anaerobic aromatic compound-degraders (Syntrophorhabdus sp.) are enriched at the end of the remediation process (Nicomrat et al, 2006;Falagán et al, 2017;Vasquez et al, 2018;Roth et al, 2019).…”
Section: Amd Remediation Technologies and Microbial Community Structurementioning
confidence: 99%
“…Similarly, passive bioremediation system enriched with Ignavibacterium, Pelotomaculum, and Petrimonas and species known to catalyse the dissimilatory reduction of ferric iron (Geobacter psychrophilus), oxidation of sulfur (Polaromonas hydrogenivorans, Flavobacterium johnsoniae, Dechloromonas aromatica, Novosphingobium sediminicola, Clostridium saccharobutylicum, and Pseudomonas extremaustralis), and reduction of nitrate (Sulfuricella denitrificans, A. ferrooxidans, and Acidithiobacillus thiooxidans), methylotrophs (methane/methanol-oxidizers), and anaerobic aromatic compound-degraders (Syntrophorhabdus sp.) are enriched at the end of the remediation process (Nicomrat et al, 2006;Falagán et al, 2017;Vasquez et al, 2018;Roth et al, 2019).…”
Section: Amd Remediation Technologies and Microbial Community Structurementioning
confidence: 99%
“…The reduction of microbial diversity in the local environments, due to the release of TOPs and HTEs from coal mining, processing, and combustion processes, has been well documented ( Ma et al, 2016 ; Zhao et al, 2019 ; Hamidović et al, 2020 ). In addition, microbes capable of degrading PAHs [e.g., Pseudomonas putida ( Ghiorse et al, 1995 ; Herrick et al, 1997 ), Alphaproteobacteria , Betaproteobacteria , Cupriavidus , Luteimonas ( Ma et al, 2016 )] and resistant/tolerant to HTEs [e.g., Proteobacteria, Firmicutes ( Huang et al, 2019 ; Roth et al, 2019 ; Zhao et al, 2019 ), Acidobacteria, Bacteroidetes ( Roth et al, 2019 ; Zhao et al, 2020 )] have been found in coal-contaminated soils and sediments. While the effects of HTEs and TOPs on microorganisms in coal-contaminated environments have received considerable attention, the ecological consequences of the complex combined pollution associated with coal wastes on microbial assemblages in natural settings, especially aquatic environments, remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the genera Caldithrix , Ignavibacterium , Limnobacter , Phycisphaera , Solitalea , and Sphaerobacter were reported to be capable of reducing nitrite or nitrate, which also showed the highest relative abundance under the micro-aerobic condition. 19–23 Fig. 4B shows that Caldilineaceae and Anaerolineaceae that belong to the Chloroflexi phylum were the dominant heterotrophic families among the three systems.…”
Section: Resultsmentioning
confidence: 97%